Growth inhibition of SK-MEL-30 human melanoma cells by antisense c-myc oligonucleotides delivered by poly(N-isopropylacrylamide)/poly(ethyleneimine) copolymer - Dincer, S.; Oskay, E. K.; Piskin, A. K.; Zeybek, N. D.; Piskin, E. (WILEY, 2010)
The c-myc oncogene has been shown to be overexpressed in a number of malignancies and plays a key role in the abnormal growth regulation of melanoma cells. This study aimed to provide an efficient system for the in vitro manipulation of c-myc expression by antisense oligonucleotides. Therefore, we used poly(NIPA)/PEI2B copolymer as vector in order to improve the intracellular availability and stability of AS ODNs. We targeted oligonucleotide sequences within the human c-myc mRNA as free AS ODNs or conjugated with a thermosensitive copolymer, in an effort to inhibit the growth of human melanoma cells. The conjugates adopted more positive charge and smaller size at 37 degrees C and they had no toxic effects on human fibroblast cells. The conjugated AS ODNs showed increased antiproliferative effect on melanoma cells as compared to free AS ODNs. At a concentration of 100 ng, AS ODNs inhibited SK-MEI, 30 human melanoma cell line proliferation maximally by 18.6%, whereas the same amount of conjugated AS ODN provided 52% inhibition. The greatest inhibition was obtained by conjugates having a polymer : AS ODN ratio of 9. Greatest inhibition was detected at 48 h and decreased after 96 h, which may be due to the depletion of AS ODNs. The results confirm the enhanced antiproliferative effects of poly(NIPA)/PEI2B-conjugated AS ODNs, which may provide improved intracellular availability for c-myc-directed antisense strategies. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: AS ODN; non-viral vectors; c-myc; temperature-sensitive polymer; N-isopropylacrylamide; poly(ethyleneimine); GENE DELIVERY; IN-VITRO; EXPRESSION; PROLIFERATION; TRANSFECTION; TRANSPORT; ONCOGENE; POLYMERS; VECTORS; Cell Biology; Biotechnology & Applied Microbiology; Engineering